3D Hierarchical Microballs Constructed by Intertwined MnO@N‐doped Carbon Nanofibers towards Superior Lithium‐Storage Properties. Issue 38 (7th June 2018) - Li, Yi‐Jing; Fan, Chao‐Ying; Li, Huan‐Huan; Huang, Ke‐Cheng; Zhang, Jing‐Ping; Wu, Xing‐Long
Abstract: MnO is a promising high‐capacity anode material for lithium‐ion batteries (LIBs), but pristine material suffers short cycle life and poor rate capability, thus hindering the practical application. In this work, a new type of porous MnO microballs stringed with N‐doped porous carbon (3DHB‐MnO@NC) with a well‐connected hierarchical three‐dimensional network structure was prepared by the facile self‐template method. The 3DHB‐MnO@NC electrode can effectively promote the ion/electron transfer and buffer the large volume change of electrode during the electrochemical reaction. As the anode for LIBs, the 3DHB‐MnO@NC possesses outstanding cycling performance (1247.7 mA h g −1 after 90 cycles at 200 mA g −1 ) and good rate capabilities (949.6 mA h g −1 after 450 cycles at 1000 mA g −1 ). The facile self‐template method of the prepared 3DHB‐MnO@NC composite paves a new way for practical applications of MnO in high performance LIBs. Abstract : Small balls : New MnO 3D hierarchical microballs prepared by the facile self‐template method achieves ultrafast, ultralong‐lifespan lithium storage (see figure).